Prediction of cognitive dysfunction after resuscitation – a systematic review - Mędrzycka-Dąbrowska, Wioletta A. (Postepy Kardiol Interwencyjnej, 2018)
Cardiac arrest (CA) due to cardiovascular disease is the leading cause of death in developed countries. It is estimated that over 350,000 people in Europe suffer from out-of-hospital cardiac arrest. According to the literature, the longer the episode of cardiac arrest, the greater the risk of cognitive impairment, especially short-term memory, as well as immediate and delayed recall. Other common dysfunctions include attention deficits and executive function disorders. The aim of this systematic review was to summarize current research on cognitive impairment in patients after sudden cardiac arrest. The electronic databases PubMed/MEDLINE, OVID, Web of Science, and EBSCO were searched using the following key words: ‘sudden cardiac arrest’, ‘out-of-hospital cardiac arrest’, ‘cognitive function’, ‘cognitive impairment’, ‘functional outcome’, ‘cardiopulmonary resuscitation’. The most recent studies from the last 7 years (2011–2018) were included. Cognitive disorders occurred in a broad range of cases: from 13% to even 100%. In one study, cognitive deficits did not occur at all. Amongst the reviewed articles only two studies were carried out on a large group of patients. The remaining studies were conducted on a small group of respondents; therefore there was no possibility to generalize the results to the entire population. The areas in which the most cognitive impairment occurred were memory, executive functions and visual–motor skills. One of the conclusions derived from the reviewed literature is the importance of continuous training of cognitive functions, especially for people with cardiovascular risk.